The Cellular Processing Capacity Limits the Amounts of Chimeric U7 snRNA Available for Antisense Delivery - Agathe Eckenfelder; Julie Tordo; Arran Babbs; Kay E Davies; Aurélie Goyenvalle; Olivier Danos (Elsevier, 2012)
Many genetic diseases are induced by mutations disturbing the maturation of pre-mRNAs, often affecting splicing. Antisense oligoribonucleotides (AONs) have been used to modulate splicing thereby circumventing the deleterious effects of mutations. Stable delivery of antisense sequences is achieved by linking them to small nuclear RNA (snRNAs) delivered by viral vectors, as illustrated by studies where therapeutic exon skipping was obtained in animal models of Duchenne muscular dystrophy (DMD). Yet, clinical translation of these approaches is limited by the amounts of vector to be administered. In this respect, maximizing the amount of snRNA antisense shuttle delivered by the vector is essential. Here, we have used a muscle- and heart-specific enhancer (MHCK) to drive the expression of U7 snRNA shuttles carrying antisense sequences against the human or murine DMD pre-mRNAs. Although antisense delivery and subsequent exon skipping were improved both in tissue culture and in vivo, we observed the formation of additional U7 snRNA by-products following gene transfer. These included aberrantly 3' processed as well as unprocessed species that may arise because of the saturation of the cellular processing capacity. Future efforts to increase the amounts of functional U7 shuttles delivered into a cell will have to take this limitation into account.